Phenotypic and Complete Reference Whole Genome Sequence Analyses of Two Paenibacillus spp. Isolates from a Gray Wolf (Canis lupus) Gastrointestinal Tract - Jessika L. Bryant; Jennifer McCabe; C. Cristoph Klews; MiCayla Johnson; Ariel N. Atchley; Thomas W. Cousins; Maya Barnard-Davidson; Kristina M. Smith; Mark R. Ackermann; Michael Netherland; Nur A. Hasan; Peter A. Jordan; et al. (Veterinary Sciences)
Inflammatory bowel disease (IBD) is increasing among mammals around the world, and domestic dogs are no exception. There is no approved cure for canine IBD with limited treatment options. Novel probiotic bacteria discovery from free-ranging animals for the treatment of IBD in domestic pets can likely yield promising probiotic candidates. Consequently, the overall aim was to isolate bacteria from free-ranging animals that could potentially be utilized as novel probiotics. Two bacteria identified as unique Paenibacillus spp. strains by small ribosomal RNA (16S) gene sequencing were isolated from the gastrointestinal tract of a North American Gray Wolf (Canis lupus). The bacteria were typed as Gram-variable, and both were catalase/oxidase positive as well as sensitive to commonly used antibiotics. The bacteria digested complex carbohydrates and lipids by standard assays. The isolated bacteria also inhibited the growth of Staphylococcus aureus and Micrococcus luteus. The whole genome sequence (WGS) length of bacterial isolate ClWae17B was 6,939,193 bp, while ClWae19 was 7,032,512 bp, both similar in size to other Paenibacillus spp. The genomes of both bacteria encoded enzymes involved with the metabolism of complex starches and lipids, such as lyases and pectinases, along with encoding antimicrobials such as lanthipeptides, lasso peptides, and cyclic-lactone-autoinducers. No pernicious virulence genes were identified in the WGS of either bacterial isolate. Phylogenetically, the most closely related bacteria based on 16S gene sequences and WGS were P. taichungensis for ClWae17B and P. amylolyticus for ClWae19. WGS analyses and phenotypic assays supported the hypothesis that the isolates described constitute two novel candidate probiotic bacteria for potential use in dogs.